Kiprah Perempuan di Masa Kesultanan Banjar: Sebagai Aktor Intelektual Hingga Memimpin Rakyat - Noor Hasanah; Raudatul Jannah (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Gender discrimination has been around for a long time. Interestingly in Banjar, at the elite level, women are actually entrusted to play an active role in the public sphere. Such as an intellectual actor in the development of Islamic knowledge and as a leader. This role was played by Fatimah, Putri Mayang Sari, Nyai Kumala Sari, and Ratu Zaleha. Everyone has their own role in their era. The writing of this article uses the library method, by applying 4 steps, that are heuristics, verification or source criticism, interpretation, and historiography. The results of the study indicate that historically Banjar women, at the elite level, have had opportunities and open roles to be able to contribute to the public sphere. The implementation of this role relies on clarity of thought, flexibility of knowledge, courage to take risks, and the ability to read situations and understand social conditions. Thus, the role and contribution of women in various fields cannot be denied and underestimated. The role and contribution of Banjar women needs to be disclosed more broadly, because studies related to this matter are still limited.